1995
DOI: 10.1164/ajrccm.152.1.7599812
|View full text |Cite
|
Sign up to set email alerts
|

Re-intubation increases the risk of nosocomial pneumonia in patients needing mechanical ventilation.

Abstract: In order to confirm that re-intubation can be a risk factor of nosocomial pneumonia in mechanically ventilated patients, a case-control study was performed. Forty consecutive patients needing re-intubation were selected as cases. Each case was paired with a matched control for the previous duration of mechanical ventilation (+/- 2 d). Nineteen (47%) of the cases developed pneumonia after re-intubation compared with 4 (10%) of the controls (odds ratio [OR] = 8.5; 95% confidence interval [CI] 1.7 to 105.9; p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
224
2
17

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 464 publications
(260 citation statements)
references
References 10 publications
9
224
2
17
Order By: Relevance
“…Other studies have reported that extubation failure increases the risk of pulmonary complications, mortality, duration of MV, and an increased length of ICU stay (5,6,17). The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies have reported that extubation failure increases the risk of pulmonary complications, mortality, duration of MV, and an increased length of ICU stay (5,6,17). The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20).…”
Section: Discussionmentioning
confidence: 99%
“…The need for reintubation is a risk factor for the development of pulmonary infection (5,18,19) because it favors bronchoaspiration and alterations in mucociliary clearance, which may lead to bacterial contamination and colonization of the airways (14,20). Also, extubation failure is directly related to altered level of consciousness (2), probably due to the fact that patients with a lower level of consciousness exhibit large amounts of secretions, cough deficiency and swallowing deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Appropriate securing of tracheal tubes and the prevention of the need for reintubations may reduce the risk of VAP [88].…”
Section: Unplanned Extubationsmentioning
confidence: 99%